2022
DOI: 10.1186/s12888-022-03829-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of suicide attempts in high-risk populations: a cross-sectional study among patients receiving opioid agonist therapy in Norway

Abstract: Background Death by suicide in patients enrolled in opioid agonist therapy (OAT) is a major clinical concern. However, little knowledge exists regarding suicide attempts in this patient group. This study presents the lifetime prevalence of suicide attempts and the associations between suicide attempts and clinical and sociodemographic variables such as education, sex, early onset of substance use (< 13 years of age), substance use patterns, and injecting substance use among patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Ukrainian data are consistent (although it is essential to mention the difference in data gathering methodology and time frame of prevalence) with those recently found across the globe. Thus, US adults with OUD self-reported past 12-month thoughts of killing oneself in 29.8% of cases in 2020 [47]; among OAT centers' participants interviewed in 2021 in Nepal, lifetime suicidality was observed in 26.0% of cases [48]; 41% of the OAT patients in Norway surveyed during 2016-2020 had attempted to die by suicide at least once during their lifetime [49].…”
Section: Discussionmentioning
confidence: 99%
“…Ukrainian data are consistent (although it is essential to mention the difference in data gathering methodology and time frame of prevalence) with those recently found across the globe. Thus, US adults with OUD self-reported past 12-month thoughts of killing oneself in 29.8% of cases in 2020 [47]; among OAT centers' participants interviewed in 2021 in Nepal, lifetime suicidality was observed in 26.0% of cases [48]; 41% of the OAT patients in Norway surveyed during 2016-2020 had attempted to die by suicide at least once during their lifetime [49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than half of people with SUD suffer from substantial mental health symptoms of psychological distress, like fearfulness, tension, worthlessness, sleeping problems, and hopelessness 3 . These symptoms have a significant impact on health-related quality of life and well-being 4 6 , where the prevalence is particularly associated with the utilization of benzodiazepines, opioids, and cannabis, as well as underlying mental and somatic disorders 4 , 7 9 . HCV infection by itself is also associated with certain extrahepatic events, such as neurological and psychiatric complications 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that up to 80% of patients receiving OAT or injecting substances have been infected with HCV, and up to 70% have at least one mental health disorder 12 – 14 . Challenges related to health and life situations, such as suicidal ideation, high fatigue levels, and unstable living conditions, may worsen psychological distress and impact HCV treatment adherence 5 , 6 . Some observational studies have suggested that HCV treatment may reduce mental health symptoms, but the studies are prone to confounding and biases limiting any causal interpretations 11 , 15 .…”
Section: Introductionmentioning
confidence: 99%